Carbon Nanotubes: A Novel Approach for Cancer Diagnosis and Therapy - Asha, ML; Ghorai, Laboni; Rajarathnam, Basetty N; Kumar, HM Mahesh; Lekshmy, J; Jasti, Srilakshmi (Journal of Orofacial Research, 2015)
Head and neck cancer is the 6th most common cancer worldwide, accounting for 5 to 6% of all cancer cases. Surgical resection and/or radiotherapy have long been regarded as the standard treatment, while chemotherapy can be added as an adjunct. However, conventional chemotherapy has certain drawbacks like nonspecific distribution, short circulation time, and tumor resistance. Recently, targeted therapeutics with nanoparticles have emerged as promising alternatives to overcome these drawbacks of conventional approaches and among the diverse classes of nanomaterials, carbon nanotubes (CNTs), due to their unique physicochemical properties, have become a popular tool in cancer diagnosis and therapy. Carbon nanotubes are tubular materials with nanometer-sizeddiameters and axial symmetry, with unique properties, such as ease of cellular uptake, high drug loading, and thermal ablation, which render them useful for cancer therapy. The important biomedical applications of CNTs include their contribution in the field of drug delivery, thermal therapy, photodynamic therapy,gene delivery, biological detection, and imaging. More recently, they have also been used as vehicles for antigen delivery, a novel immunization strategy against infectious diseases and cancer. These multifunctional and multiplex nanoparticles are now being actively investigated and are on the horizon as the next generation of nanoparticles, facilitating personalized and tailored cancer treatment. However, concerns over certain issues, such as biocompatibility and toxicity have been raised and warrant extensive research in this field.